The Impact of HIV Infection on Society's Perception of Clinical Trials - Levine, Robert J. (Kennedy Institute of Ethics journal, 1994)
All international codes of research ethics and virtually all national legislation and regulation in the field of research involving human subjects project an attitude of protectionism. Written with the aim of avoiding a repetition of atrocities like those committed by the Nazi physician-researchers, calamities like the thalidomide experience, or ethical violations like those of the Tuskegee syphilis study, their dominant concerns are the protection of individuals from injury and from exploitation. In recent years, however, society's perception of clinical research has shifted dramatically. Now, largely as a consequence of the efforts of the AIDS activists, clinical research is widely perceived as benign and beneficial. Although this shift in attitude has resulted in some important improvements in research policies and practices, this new perception is just as wrong-headed as was the earlier excessive protectionism. It is necessary to maintain a balanced perspective; our policies should encourage the conduct of ethical research while maintaining the vigilance necessary to safeguard the rights and welfare of the subjects.